'Choreopiscopally': James Joyce's 'Nausicaa' and Vaslav Nijinsky's The Afternoon of a Faun. Issue 1 (February 2022) - Argyrides, Patty
Abstract : One striking commonality between Vaslav Nijinsky's The Afternoon of a Faun (1912) and the 'Nausicaa' chapter in James Joyce's Ulysses (1922) is that both culminate with masturbation scenes and were met with similar reactions – outrage and censorship. Upon closer consideration, the similarities between Faun and Ulysses reach far beyond the climactic solos of Leopold Bloom and Nijinsky as the Faun. In Ulysses, Joyce choreographs the words on the page, the fictional bodies of his characters' movements through Dublin, and elicits embodied responses from his readers. Using 'Nausicaa' and Faun as my case study, I reveal the significant parallels between Nijinsky and Joyce as they both present their vision of modernity through the body. As a former dancer, I understand, physically the innovation to the form of ballet Nijinsky sought after. My methodology therefore combines my embodied knowledge of ballet along with an analysis of literature.